Miramistin effect on BHK-21 and PSGK-30 cell line proliferation and FMD virus reproduction in these cells - M. I. Doronin; D. A. Lozovoy; V. V. Pronin; D. V. Mikhalishin; V. A. Starikov; A. V. Borisov; A. A. Shishkova (Ветеринария сегодня)
At present, Miramistin drug (benzyldimethyl [3-(myristoylamino) propyl] ammonium chloride monohydrate), which has a broad bactericidal effect, is used in veterinary practice. This antiseptic is active against most viruses, mycoplasmas, bacteria, fungi and protozoa. According to toxicometric parameters, Miramistin is classified as a low-hazard substance. Use of cell structures as test systems for assessing the toxicity of pharmacological substances instead of conventional tests on experimental animals allows us to better clarify the possible mechanism of the effect of the investigated substance. Since many types of mycoplasmas affect the genitourinary system organs, to assess the cytotoxicity of Miramistin kidney mammalian cells of various mammals can be used as test systems, in particular, the newborn Syrian hamster (VNK-21), Siberian mountain ibex (PSGK-30), and others. The possibility of using BHK-21 and PSGK-30 cell monolayer as test systems for assessing the baseline cytotoxicity of Miramistin was shown. When studying toxicity of the drug, the effect of its various concentrations on the cell morphology was studied, the number of viable cells and the total protein content were determined as an indicator of the cell mass increase. The results of a cytomorphological study indicate that the Miramistin maximum permissible concentration of for BHK-21 and PSGK-30 cell monolayer is 25 μg/cm3. The use of this antibacterial drug in higher concentrations caused the appearance and increased signs of endogenous intoxication and degeneration. When evaluating the proliferative activity of cells under the influence of the Miramistin antibiotic in different concentrations, it was found that increasing the dose to 50, 75, 100, 125, 150 μg/cm3 leads to decrease in the rate of cell growth compared to the control. The Miramistin content in the growth medium in an amount of up to 25 μg/cm3 did not affect the intensity of protein synthesis. Presence of Miramistin in the culture medium at the maximum permissible concentration causes a slight decrease in the reproduction of foot and mouth disease virus in BHK-21 and PSGK-30 cell cultures by 4.5 and 4.0%, respectively, compared with the control without antibiotic. Since mycoplasmas are the most common contaminants of cell cultures, further studies will be aimed at exploring the possibility of using Miramistin for decontamination of BHK-21 and PSGK-30 cell monolayers.